Explaining the Antecedents and Consequences of the Glass Cliff in Service Organizations - Sara Kavoosi; Ali Safari; Ali Shaemi Barzoki (مدیریت دولتی)
Objective The concept of the "glass cliff" refers to the observed trend of appointing women to leadership roles in contexts that are inherently risky or crisis-prone. This phenomenon posits that women are disproportionately likely to be placed in precarious management positions where the risk of failure is high. The exploration of the glass cliff can catalyze further scholarly inquiry and stimulate discussions concerning the specific challenges and obstacles that women encounter in leadership positions. The primary objective of this research is to meticulously design a detailed model of the glass cliff, focusing particularly on its antecedents and consequences, within the context of service organizations located in Golestan province. Methods The research is developmental in its intent and employs a mixed-methods sequential exploratory design, integrating both qualitative and quantitative approaches. Participants in the qualitative phase comprised both male and female managers working in various service organizations across Golestan province, alongside university professors. Upon reaching theoretical saturation, twenty individuals were selected through a combination of purposeful and snowball sampling methods. Insights gathered from the qualitative phase were subsequently transformed into a coherent set of propositions and hypotheses, which were rigorously tested in the quantitative phase. Through in-depth analysis of the interviews conducted, a comprehensive model outlining causal relationships was formulated. Subsequently, a structured questionnaire containing 39 items was developed from the qualitative data. This questionnaire was meticulously validated for reliability and validity before being distributed among female managers in service organizations through a carefully stratified random sampling method. Ultimately, 225 completed questionnaires were collected and their data subjected to analysis using structural equation modeling and confirmatory factor analysis, facilitated by the Smart PLS software. Results The developed model encompasses several elements: causal factors such as characteristics of women's leadership, criteria for meritocracy, women’s preferences, and organizational factors; the central phenomenon of the glass cliff; strategic responses including succession planning, personal development, and support networks; and outcomes, which are categorized as positive and negative consequences at both individual and organizational levels. The analysis of the data conclusively showed that factors such as women's leadership characteristics, meritocracy criteria, women’s preferences, and organizational dynamics have a significant impact on the glass cliff phenomenon. Moreover, the influence of the glass cliff on strategies such as succession planning, personal development, and support networks was robustly confirmed. Drawing from the qualitative aspect of the study, it is recommended that decision-makers and senior managers in service organizations diligently consider the origins of the glass cliff phenomenon and actively engage in managing the factors that contribute to the unique challenges faced by women in high-risk managerial positions Conclusion This investigation stands as one of the initial studies that, by leveraging a hybrid research methodology, provides a comprehensive framework to thoroughly understand the causal conditions, strategic responses, and consequences of the glass cliff phenomenon.